2021
DOI: 10.2337/db20-1031
|View full text |Cite
|
Sign up to set email alerts
|

Perirenal Fat Thickness Is Significantly Associated With the Risk for Development of Chronic Kidney Disease in Patients With Diabetes

Abstract: Perirenal fat is adjacent to kidneys and active in metabolism and adipokine secretion. We aimed to investigate whether perirenal fat is an independent predictor for chronic kidney disease (CKD) and compared it with total, subcutaneous, or visceral fat in patients with diabetes. Perirenal fat thickness (PRFT) was measured by computed tomography, and total body fat (TBF), subcutaneous adipose tissue (SAT), and visceral adipose tissue (VAT) were assessed by DEXA. In cross-sectional analysis, patients with higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…have also demonstrated that PrFT can be a reliable method for the quantification of fatty liver as well as for the quantification of visceral fat ( 30 ). Increasing evidence have suggested that the accumulation of perirenal fat increases the risk for the development of chronic kidney disease through decreasing the eGFR level and increasing the excretion rate of urinary protein ( 31 33 ). The results in our study were consistent with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…have also demonstrated that PrFT can be a reliable method for the quantification of fatty liver as well as for the quantification of visceral fat ( 30 ). Increasing evidence have suggested that the accumulation of perirenal fat increases the risk for the development of chronic kidney disease through decreasing the eGFR level and increasing the excretion rate of urinary protein ( 31 33 ). The results in our study were consistent with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also found that the relationship between PrFT and PnFT and SUA was not significant in patients with reduced renal function. It was reported that PrFT was independently and positively associated with renal function [ 18 , 19 ]. This finding indicates that the effect of PrFT on SUA may be independent on reduced renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Paranephric fat, lied adjacent to perirenal fat, was not wrapped by renal fascia and was a typical white adipose tissue [ 17 ]. Multiple studies demonstrated that single perirenal fat was significantly associated with metabolic syndrome, renal function [ 18 , 19 ] as well as atherosclerosis [ 20 , 21 ]. Para-perirenal fat, which means the sum of perirenal fat and paranephric fat, was independently related to blood pressure [ 22 ] and reduced renal function [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the Kidney, ectopic fat often deposits in the perirenal space, renal sinus, and renal parenchyma (12). Previous studies (13)(14)(15) have confirmed that perirenal and renal sinus fat deposition is closely related to the increased risk of CKD, but the relationship between renal parenchymal fat deposition and CKD in patients with T2DM remains unclear.…”
Section: Introductionmentioning
confidence: 98%